THE RELATIONSHIP BETWEEN KNOWLEDGE AND MATERNAL BEHAVIOR IN HANDLING ORAL TRUSH IN INFANTS AGED 3-14 DAYS - Nuraeni, Elsa Hani; Siantar, Rupdi Lumban; Junita, Friska (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Oral thrush in infants can be common, especially in newborns up to 14 days of age. The mother's role in dealing with oral thrush in infants has a significant influence in the healing process and prevention of further infection. This study aims to examine the correlation between maternal knowledge and behavior in dealing with oral thrush in infants aged 3-14 days at Cikarang Medika Hospital. The research method used was a cross-sectional approach with a population of 37 mothers who had babies aged 3-14 days at Cikarang Medika Hospital, and the entire population was taken as a sample (total sampling). Data were collected through questionnaires and analyzed using frequency distribution and chi-square test. The results showed that most mothers had good knowledge about oral thrush in infants of this age (37.8%), and the majority of them showed good behavior in handling it (51.4%). There was a significant correlation between mothers' knowledge and behavior in managing oral thrush in infants aged 3-14 days at Cikarang Medika Hospital (ρ = 0.002). Thus, it was concluded that improved educational programs and support to mothers are needed to reduce the incidence of oral thrush, including counseling, clearer presentation of educational materials, and motivation to improve maternal compliance and understanding in managing the condition